Fabrication and Characterization of Tungsten-Modified TiO2 as a Photo-Anode in a Dye-Sensitized Solar Cell - Ming-Cheng Kao; Jun-Hong Weng; Chih-Hung Chiang; Kai-Huang Chen; Der-Yuh Lin; Tsung-Kuei Kang (Engineering Proceedings, 2025)
The tungsten (W)-modified TiO2 films were fabricated on the fluorine-doped TiO2 substrates using the sol–gel process. The influences of W dopant on the photovoltaic properties of the tungsten-modified TiO2 DSSC were analyzed, too. The crystallization and dye absorption of tungsten-modified TiO2 thin films increased more than those of the undoped TiO2 thin films. Furthermore, the optimal performances of the Voc, Jsc, fill factor, and efficiency of the DSSC with tungsten-modified TiO2 thin films were 0.68 V, 16.28 mA/cm2, 65.5%, and 7.03%, respectively. The enhancement was mainly due to the improved crystallinity and increased dye adsorption of the tungsten-modified TiO2 thin films, which contributed to improving the efficiency of the dye-sensitized solar cell.